Coexistence of Two Cubic-Lattice Co Matrices at High Temperatures in Co-Re-Cr-Ni Alloy Studied by Neutron Diffraction. (17th May 2018) - Beran, Přemysl; Mukherji, Debashis; Strunz, Pavel; Gilles, Ralph; Hölzel, Markus; Rösler, Joachim
Abstract : In situ neutron diffraction measurements were performed during heating to high temperature and cooling for a Co-17Re-23Cr-25Ni alloy. The allotropic transformation of the Co matrix and the evolution of the low-temperature hexagonal and high-temperature cubic Co phases were studied. A surprising observation was the splitting of the face-centred cubic (fcc) Co phase peaks at high temperature during heating as well as cooling. The phase evolution was monitored, and an appearance of the secondary fcc phase could be linked to the formation of σ phase (Cr2 Re3 type) associated with a compositional change in the matrix due to diffusion processes at high temperature.